2009
DOI: 10.48550/arxiv.0911.0931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformal Dynamics for TeV Physics and Cosmology

Francesco Sannino

Abstract: We introduce the topic of dynamical breaking of the electroweak symmetry and its link to unparticle physics and cosmology. The knowledge of the phase diagram of strongly coupled theories plays a fundamental role when trying to construct viable extensions of the standard model (SM). Therefore we present the state-of-the-art of the phase diagram for SU , Sp and SO gauge theories with fermionic matter transforming according to arbitrary representations of the underlying gauge group. We summarize several analytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
194
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 115 publications
(196 citation statements)
references
References 310 publications
2
194
0
Order By: Relevance
“…Besides the possibility of infrared fixed points recently it has been discovered that nonsupersymmetric gauge theories with fermionic matter at large number of flavors develop ultraviolet fixed points [10]. Furthermore, as soon as it was discovered that theories with an extremely low number of matter flavors were able to lead to large distance conformality and potentially become excellent candidates of models of dynamical electroweak symmetry breaking, the question whether these theories could feature light composite scalars was addressed in [14][15][16]. These papers rekindled the long debate on the existence of a light scalar compared to the intrinsic scale of the theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the possibility of infrared fixed points recently it has been discovered that nonsupersymmetric gauge theories with fermionic matter at large number of flavors develop ultraviolet fixed points [10]. Furthermore, as soon as it was discovered that theories with an extremely low number of matter flavors were able to lead to large distance conformality and potentially become excellent candidates of models of dynamical electroweak symmetry breaking, the question whether these theories could feature light composite scalars was addressed in [14][15][16]. These papers rekindled the long debate on the existence of a light scalar compared to the intrinsic scale of the theory.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of arguments has been used in favor of the existence of a light scalar, not associated to Goldstone bosons linked to the spontaneous breaking of global symmetries. Furthermore, there has been used a number of methods ranging from the use of the saturation of the trace and axial anomaly [18] to supersymmetry [14,[19][20][21], alternative large N limits [16,22] as well as gauge-gauge duality [23][24][25][26]. Other interesting attempts to investigate the dynamics associated to light scalars in near conformal field theories appeared in the literature [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…A review of these models and the phase diagram of strongly coupled theories can be found in Ref. [37]. A relevant point is that the technicolor dynamics is strongly modified by the new interactions necessary to give masses to SM fermions [38] and the interplay between these two sectors leads to an entirely new class of models, constraints on which were discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In this section we will move to considering gauge theories with the matter fields distributed in two distinct and inequivalent representations of the gauge group. Such theories are starting to become of interest because they may play role in composite higgs [64], composite dark matter [65] and composite inflation [66] models. As a result there are already some lattice simulation of such theories.…”
Section: Two-representation Theoriesmentioning
confidence: 99%